Kidney Transplantation From Uncontrolled Donation After Circulatory Death Maintained by Normothermic Regional Perfusion: An 8-Year Portuguese Single-Centre Experience - Ana Pinho; Susana Sampaio; Susana Sampaio; Inês Alencastre; Maria João Polidoro; Maria João Polidoro; Margarida Rios; Roberto Roncon-Albuquerque; Roberto Roncon-Albuquerque; João Silva; João Silva; Carlos Silva; et al. (Transplant International)
In January 2016, our hospital started a program of uncontrolled donation after circulatory death (uDCD) to increase organ availability for kidney transplantation. We analysed the results of 523 consecutive kidney transplants (KT) performed from January 2016 to December 2023 in our center and compared the outcomes of 142 KT from uDCD maintained by abdominal normothermic regional perfusion (A-NRP) with those from 194 KT from standard-criteria brain-death donors (SCD) and 187 KT from expanded-criteria brain-death donors (ECD). Primary non-function (PNF) was similar in uDCD (16.9%) and ECD (13.4%, p = 0.460) and more common than in SCD (4.6%; p < 0.001). In addition, delayed graft function (DGF) differed among the groups, being higher in the uDCD (69.7%), followed by ECD (43.9%) and SCD (37.6%; p ≤ 0.05). However, the estimated glomerular filtration rate (eGFR) at 7 years was similar in uDCD and SCD (62.27 ± 18.38 mL/min/1.73 m2 vs. 65.48 ± 19.24 mL/min/1.73 m2, p = 1) and higher than in ECD (47.67 ± 23.05 mL/min/1.73 m2, p < 0.001). When excluding PNF, the 7-year death-censored graft survival was similar among the three groups (SCD, 91.4%; uDCD, 96.2%; ECD, 82.7%). Despite the increased risk of PNF and DGF, functional and survival outcomes of uDCD KT at 7 years were comparable to those of SCD, thus supporting the use of uDCD kidneys maintained under A-NRP as a successful resource to address organ scarcity.